2005
DOI: 10.1007/s10551-005-2925-y
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Sensitivity for Organizational Communication Issues: Examining Individual and Organizational Differences

Abstract: This descriptive study discusses cognitive mapping as a technique for analyzing ethical sensitivity, examines whether the method allows comparisons between people, compares the ethical sensitivity levels of participants from three organizations, examines which indicators of ethical sensitivity are most salient to members of specific organizations, and examines whether education level or organizational membership is the best predictor of an individual's ethical sensitivity level. Subjects from three organizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 49 publications
0
13
0
4
Order By: Relevance
“…As proposed in human capital theory (Becker, 1964), formal education is a short-hand signal to organizations of individuals' abilities, accumulated knowledge, and desired personal attributes like diligence (Ceci, 1991;Swenson-Lepper, 2005). As such, formal education is highly rewarded in the labor market.…”
Section: Education Levelmentioning
confidence: 99%
“…As proposed in human capital theory (Becker, 1964), formal education is a short-hand signal to organizations of individuals' abilities, accumulated knowledge, and desired personal attributes like diligence (Ceci, 1991;Swenson-Lepper, 2005). As such, formal education is highly rewarded in the labor market.…”
Section: Education Levelmentioning
confidence: 99%
“…On the individual level, Scott and Willits () also identify education as the strongest predictor of proenvironmental tendencies in a person's behavior and opinions. Based on his research, Swenson‐Lepper () comes to the conclusion that education appears to be an aspect that influences an individual's ethical sensitivity strongly. This finding receives support by Hillcoat, Forge, Fien, and Baker (), who conduct focus group interviews and find that with increasing education and awareness young people report to feel more empowered to engage in proenvironmental behavior.…”
Section: Choice and Calibration Of Antecedent Conditionsmentioning
confidence: 99%
“…Research by Bebeau (1994) on ethical sensitivity in the field of dentistry indicated that individuals in professional areas that require higher education (dentist versus hygienist) incline to demonstrate higher levels of ethical sensitivity. Using a cognitive mapping technique, Swenson-Lepper (2005) found that level of education is positively correlated with moral sensitivity. Examining major factors influencing consumers' intention to buy advertised green products, Chan (2004) argued that consumers' educational level is a significant determinant of green purchase intention.…”
Section: Educational Level and Environmental Performancementioning
confidence: 99%